OPERATORS ON THE BESOV SPACES OF HOLOMORPHIC FUNCTIONS ON THE UNIT BALL IN C^n
In the present paper we consider the Toeplitz-T_h ^ α and differentiation-D^δ operators on the Besov spaces B_p(β) for all 0< p<∞. We show that T_h ^ α: B_p(β)→ B_p(β) for hH^∞(B^n) and D^δ :B_p(β)→ B_p(β), where β=β +pδ . , number=2 (243), journal=Proceedings of the YSU A: Physical and Mathematical Sciences, author=Harutyunyan, A.V. and Lusky, W., year=2017, month=Aug., pages=139–145